MODEL "LEARNING CYCLE" TO INCREASE STUDENT CRITICAL THINKING ON LEARNING CONCEPT OF IPS LEARNING ENVIRONMENT IN ELEMENTARY SCHOOL - Rana Gustian Nugraha; fajar Kusumah solihin (Jurnal Pesona Dasar, 2017)
The purpose of the research is to improve student’s critical thinking on the concept of maintaining the environment in Elementary School by using the learning cycle model. The research approach is used qualitative research, and the research method is used action research class (PTK) by using Kemmis and Mc. Taggart design. The participants were all students class III SDN Parakanmuncang 1, academic year 2016-2017. The results showed an increasing in learning outcomes that were shared in various aspects: cognitive, affective, and psychomotor aspects. The use of the learning cycle model makes the process of significant change. The use of learning cycle model in IPS learning on the concept of natural and artificial environment was able to improve the critical thinking skill of students and able to improve student learning outcomes. It can be proven from the individual evaluation of each cycle in each action. The results of the average grade values individually are as follows; cycle 1 reached 43.45, on the implementation of cycle 2 reached 58.25, and on the last implementation of the cycle 3 reached 74.8. Which means there is an increase in learning outcomes IPS of students class III SDN Parakanmuncang 1 after using the learning cycle model